Uwagi o języku polskim i dawnej sytuacji językowej w Daublach na Brasławszczyźnie - Rieger, Janusz A. (Slavistica Vilnensis, 2009)
Professor Chekmonas has demonstrated how an examination of one person reveals the essential features of their language as well as the language of the village in which they live. Also, that casts light on the linguistic history of the village and its environs. In this article, the author employs the same technique, yet on a micro scale. The western part of the Braslau region used to be differentiated in terms of its linguistic nature: the region was populated by Lithuanians, Belarusians and Poles. Thus the Belarusian dialects are based on the Lithuanian substratum, while the Polish dialects are based on Lithuanian and Belorussian. An informant from the Polish nobility tells us about the Lithuanian villages, the Lithuanian language as spoken by the older generations of Poles, and the current situation of the Polish language. His language contains many Belorussian peculiarities, some common Lithuanian-Belarusian features, and probably one purely Lithuanian feature.There is a need for similar studies devoted to the language of other idiolects as well as to the language of the few villages the inhabitants of which still speak Polish.